L'entre-deux identitaire dans quelques oeuvres d'écrivains francophones "immigrantsË®, "cas de Dany Laferrière, d'Alain Mabanckou, de Calixthe Beyala et de Lottin WekapeË® - Kayumba, Viviane Ngoie Banza (Rhodes University, Faculty of Humanities, School of Languages and Literatures, 2019)
This dissertation examines the theme of hybrid identities in Mabanckou, Laferrière, Beyala and Wekape's novels : Black Bazar, Le Petit prince de Belleville, Je suis un écrivain japonais and J'appartiens au monde. Hybrid identity raises the issue of identity diversity and contemporary francophone literature is characterised by the emergence of fictional narratives increasingly numerous. This research undertaken is driven by the desire to extend the field of investigation in francophone literature by taking into account a varied corpus of Haitian, Congolese, and Cameroonian literatures. I have opted for writers who settled in a foreign country and have adopted a foreign language that they considered to be part of a foreign literary world; writers who are between two or more cultures which they depict in French. The few existing studies on hybrid identities on these four novels focused more on formal and linguistic analysis and omitted meaningful sociocritic analysis. It is clear that a full study on sociocritic approach on hybrid identity on these four authors remains to be done. The research is demonstrating how different characters created by these four postmodern immigrant French-speaking writers occasionally function similarly in their texts. This gives a clear understanding of the specific behaviour of immigrants characters, vis-Ã -vis their various situations in the novels, and how these immigrants seek to address the problems they encounter. As this research offers reflections related to the identities and nationalities of immigrants, Laferrière, Mabanckou, Beyala and Wekape's texts are based on the search for social belonging and a literary membership in this modern world. Therefore, they are analysing their position in a literary field as well as in a social field. In their texts they highlight the Space real or imaginary. In which way and how this Space contribute to the evolution of francophone literature? To what extent does francophone literature takes into account this representation of the Space? These questions lead to a reflection on the position occupied by these authors in the francophone field and the source of their literary inspirations. My interest in these authors is motivated by the fact that, by living and writing in a country which is not their place of birth, they each reveal different aspects of hybrid identity. Each of them, has his or her personal and original way of tackling the problem of mixed identity. They present their characters in different situations and different contexts, showing that each has been in contact with several cultures which they have assimilated and each lived in his or her own way a particular story. My study's focus is to understand the problems of contact of cultures and their consequences, and to explore how through the characters of the novel, immigrant French speaking writers understood their acculturation as themselves have experienced an identity crisis, resulting from the confrontation of the culture of their new homeland and the culture of their country of origin. For this reason, Bourdieu's approach "la sociocritique" will help me to found out the origin of the author's obsession with the question of hybrid identity. I have chosen these four immigrant speaking writers to explore the strategies implemented by the novels' narrators to construct their identities and to find out how the narrators express the intentions of the authors. In their texts, Mabanckou, Beyala, Laferrière and Wekape have used various strategies to express the quest for identity which gives clear indications of the authors' creativity such as humour, parody, or solemnity and gravity - and the narrative voices reveal distinctive attitudes in relation to hybrid identity. At this level, other approaches will also be called for, such as the work of Westphal, Doubrovsky, Genette, Colona, etc. Through my investigation, these works present similarities and dissimilarities. Each author tackled the questions of hybrid identities according to his own experience. From there, a different commitment emerges, depending on the degree of inquiry into questions about immigration. These authors all evoke the social precariousness of their characters or the immigrant and privilege an urban framework. The examination of these works allowed me to identify their place in Francophonie literature and to discover the importance of their texts. The four novels relate to the search for identity, an aesthetic way and a search for freedom. They possess aesthetic qualities, they have a high degree of coherence. Their romantic choice shows their creativity and their strategies engender a hybrid writing that stems from their position between several languages and place these novels within the world literature.
Keywords: African literature (French) -- History and criticism; Immigrants in literature; Mabanckou, Alain, 1966-. Black bazaar; LaferrieÌ€re, Dany. Je suis un écrivain japonais; Beyala, Calixthe. Le Petit prince de Belleville; Wekape, Lottin, 1968-. J'appartiens au monde